GAYA HIDUP NONGKRONG DI WARUNG KOPI PADA MAHASISWA PENDIDIKAN EKONOMI REGULER A FKIP UNTAN - Riswanda, Nur Indra; Matsum, Junaidi H; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was motivated by life student"™s lifestyle when hanging out in coffe shop that are becoming popular in student circles. In practice, the lifestyle hanging out in coffe shop can have an impact on student ecomonic reguler A FKIP Untan. This research also use a qualitative method with a case study approach, data collection techniques by interview with voice recorde on andoid and documentation. The object of this research were students of FKIP Untan economic education reguler A 2019 "“ 2020. The result of this study is that activities carried out by college student when hanging out in coofe shop, doing college chores, silaturahmi, and playing online game, measures taken to determine the student"™s lifestyle when hanging out in coffe shop using the AIO concept. Researchers also found that the intensity students of FKIP Untan economic education reguler A activities in hanging out at high coffe shop led to some consumtive behavior.